2022
DOI: 10.1021/acs.jafc.1c08072
|View full text |Cite
|
Sign up to set email alerts
|

Production of High Levels of 3S,3′S-Astaxanthin in Yarrowia lipolytica via Iterative Metabolic Engineering

Abstract: Astaxanthin is a highly value-added keto-carotenoid compound. The astaxanthin 3S,3′S-isomer is more desirable for food additives, cosmetics, and pharmaceuticals due to health concerns about chemically synthesized counterparts with a mixture of three isomers. Biosynthesis of 3S,3′S-astaxanthin suffers from limited content and productivity. We engineered Yarrowia lipolytica to produce high levels of 3S,3′S-astaxanthin. We first assessed various β-carotene ketolases (CrtW) and β-carotene hydroxylases (CrtZ) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 49 publications
1
33
2
Order By: Relevance
“…In previous studies, Ma et al (2021) constructed a Y. lipolytica strain that could produce 453 mg/L of astaxanthin in 5-L fermenter through targeting the enzyme fusions (CrtW-Z) to subcellular compartment [ 14 ]. Zhu et al (2022) adjusted the expression levels of CrtW and CrtZ, restored leucine biosynthesis, and performed fed-batch fermentation in the synthetic CSM-Ura medium supplemented with YAG concentrated medium, resulting in the production of 3.3 g/L astaxanthin [ 9 ]. Above studies enhanced the production of astaxanthin by promoting the cell growth and substrate conversion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, Ma et al (2021) constructed a Y. lipolytica strain that could produce 453 mg/L of astaxanthin in 5-L fermenter through targeting the enzyme fusions (CrtW-Z) to subcellular compartment [ 14 ]. Zhu et al (2022) adjusted the expression levels of CrtW and CrtZ, restored leucine biosynthesis, and performed fed-batch fermentation in the synthetic CSM-Ura medium supplemented with YAG concentrated medium, resulting in the production of 3.3 g/L astaxanthin [ 9 ]. Above studies enhanced the production of astaxanthin by promoting the cell growth and substrate conversion.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, using microorganisms as efficient platforms for astaxanthin production has attracted considerable attentions [ [4] , [5] , [6] ]. In relevant studies, astaxanthin titers in engineered Escherichia coli , Saccharomyces cerevisiae , and Y. lipolytica strains varied from 404.78 mg/L to 3.3 g/L in different culture scales [ [7] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods are being developed for this purpose. Thus, using the genetically modified organisms (GMO) Yarrowia lipolytica, Escherichia coli, and Saccharomyces cerevisiae, an enhancement in the synthesis of ASX to 8–10 mg/g DCW occurred [ 38 , 62 , 63 ]. However, the commercial application of these genetically modified microorganisms and the use of their products in food or feed will need to undergo special regulations to ensure their safety.…”
Section: Structure and Sources Of Astaxanthinmentioning
confidence: 99%
“…Previous work suggested that only HpCrtW initiated the biosynthesis of astaxanthin in H. pluvialis 48 and Y. lipolytica. 49 Thus, we ligated two copies of HpcrtW with one copy of HpcrtZ and then fused them with three different combinations of upstream genes: idi/hmgr, idi/ hmgr/hmgs, and idi/hmgr/crtE. All the above-mentioned vectors were transformed into strain M326 to generate engineered strains designated IRW2Z, IRSW2Z, and IREW2Z.…”
Section: Improving the Production Of Astaxanthin By Introducing A Het...mentioning
confidence: 99%